Update on antibiotic resistance in foodborne Lactobacillus and Lactococcus species - Devirgiliis, Chiara; Zinno, Paola; Perozzi, Giuditta (Frontiers in Microbiology, 2013)
Lactobacilli represent a major Lactic Acid Bacteria (LAB) component within the complex microbiota of fermented foods obtained from meat, dairy and vegetable sources. Lactococci, on the other hand, are typical of milk and fermented dairy products, which in turn represent the vast majority of fermented products. As is the case for all species originating from the environment, foodborne lactobacilli and lactococci consist of natural, uncharacterized strains, whose biodiversity depends on geographical origin, seasonality, animal feeding/plant growth conditions. Although a few species of opportunistic pathogens have been described in lactobacilli and lactococci, they are mostly non-pathogenic, Gram-positive bacteria displaying probiotic features. Since antibiotic resistant (AR) strains do not constitute an immediate threat to human health, scientific interest for detailed studies on AR genes in these species has been greatly hindered. However, increasing evidence points at a crucial role for foodborne LAB as reservoir of potentially transmissible AR genes, underlining the need for further, more detailed studies aimed at identifying possible strategies to avoid AR spread to pathogens through fermented food consumption. The availability of a growing number of sequenced bacterial genomes has been very helpful in identifying the presence/distribution of mobile elements associated with AR genes, but open questions and knowledge gaps still need to be filled, underlining the need for systematic and datasharing approaches to implement both surveillance and mechanistic studies on transferability of AR genes. In the present review we report an update of the recent literature on AR in lactobacilli and lactococci following the 2006 EU-wide ban of the use of antibiotics as feed additives in animal farming, and we discuss the limits of the present knowledge in evaluating possible risks for human health.